IMPLEMENTASI NILAI-NILAI PERJUANGAN DIPONEGORO DALAM PEMBELAJARAN IPS DI SD DIPONEGORO - Suyanti Suyanti (Universitas PGRI Madiun, 2016)
This research is aimed to investigate: 1) Teacher’s understanding about Diponegoro’s value struggle in Elementary school Diponegoro, 2).the implementation of Diponegoro’s Value Struggle on Social Learning 3) The barriers which are faced implementation Diponegoro’s value struggle in Elementary School Diponegoro. This research used descriptive qualitative method. Results of this research are: 1) teacher’s understanding about Diponegoro’s value struggle is in the form of religious attitude, honesty, care and the spirit of nasionalism. 2). Diponegoro values have been inserted into learning set.3) barriers faced by teacher in implementation Diponegoro’s value struggle as in Elementary School Diponegoro is the negative effect of globalization to the student and the lack of learning resources.